Molecular and characterization of NnPPO cDNA from lotus (Nelumbo nucifera) in rhizome browning - Dong, C; Yu, A Q; Yang, M G; Zhou, M Q; Hu, Z L (Cellular and Molecular Biology, 2016)
The complete cDNA (NnPPO) of polyphenol oxidase in Nelumbo nucifera was successfully isolated, using Rapid amplification cDNA end (RACE) assays. The full-length cDNA of NnPPO was 2069 bp in size, containing a 1791 bp open reading frame coding 597 amino acids. The putative NnPPO possessed the conserved active sites and domains for PPO function. Phylogenetic analysis revealed that NnPPO shared high homology with PPO of high plants, and the homology modeling proved that NnPPO had the typical structure of PPO family. In order to characterize the role of NnPPO, Real-time PCR assay demonstrated that NnPPO mRNA was expressed in different tissues of N. nucifera including young leave, rhizome, flower, root and leafstalk, with the highest expression in rhizome. Patterns of NnPPO expression in rhizome illustrated its mRNA level was significantly elevated, which was consistent with the change of NnPPO activity during rhizome browning. Therefore, transcriptional activation of NnPPO was probably the main reason causing rhizome browning.